Pelatihan Mendesain Storyboard untuk Produksi Iklan Visual pada Yayasan Rumah Gemilang Indonesia, Depok - Radita Gora; Siti Maryam; Maria Febiana Christianti (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
form of advertisements is a new demand for the younger generation, especially students who are assisted by the multimedia major at Rumah Gemilang Indonesia, to have skills that are up to standard for the work needs of the content provider entertainment industry. The basic skills that need to be possessed are creating and compiling concepts in the draft content design in the form of storyboards used in the pre-production of advertising content in the form of visual designs. This Community Service prepares the need for expertise in making storyboard images in a standardized format. The students are able to take part in the training and can create visual works that are drawn manually using paper and pencil. This training activity received enthusiasm from the participants who participated in service activities as a complement to skill learning in advertising media production lessons because they had never been obtained before from learning in the target places. In addition, it can also be implemented by students to make visual products made in class.